2020
DOI: 10.1177/0003489420924061
|View full text |Cite
|
Sign up to set email alerts
|

Voice-Related Quality of Life in Patients with Chronic Rhinosinusitis

Abstract: Objective: Chronic rhinosinusitis (CRS) has long been associated with vocal dysfunction. However, studies quantifying the presence of voice dysfunction in CRS patients or the effects of functional endoscopic sinus surgery (FESS) are sparse. The goal of this study was to determine the voice-related quality of life in patients undergoing FESS for CRS using the validated Voice Related Quality of Life Survey (VRQL). We correlated the preoperative VRQL scores to the Sino-Nasal Outcome Test (SNOT-22) scores, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…While we have previously demonstrated that both earand voice-related symptoms are common in patients with CRS, our study is the first to report the lack of correlation between ETDQ-7 score and VRQoL score with the CT-based severity. 11,12 Our hypothesis that certain symptoms might correlate more with posteriorly versus anteriorly draining sinuses was disproven.…”
Section: Discussionmentioning
confidence: 99%
“…While we have previously demonstrated that both earand voice-related symptoms are common in patients with CRS, our study is the first to report the lack of correlation between ETDQ-7 score and VRQoL score with the CT-based severity. 11,12 Our hypothesis that certain symptoms might correlate more with posteriorly versus anteriorly draining sinuses was disproven.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CRS has been shown to be a risk factor for both voice disorders and Eustachian tube dysfunction. 4,5 In this study we sought to identify gender-specific differences after functional endoscopic sinus surgery (FESS) on voice-related, Eustachian tube, and sinonasal QOL.…”
mentioning
confidence: 99%
“…The 22‐item Sino‐Nasal Outcome Test (SNOT‐22) test has been widely used to evaluate sinonasal quality of life (QOL); however, the SNOT‐22 is not an exhaustive evaluation of symptoms related to CRS. For example, CRS has been shown to be a risk factor for both voice disorders and Eustachian tube dysfunction 4,5 . In this study we sought to identify gender‐specific differences after functional endoscopic sinus surgery (FESS) on voice‐related, Eustachian tube, and sinonasal QOL.…”
mentioning
confidence: 99%